Influence of Parental Monitoring on Adolescents’ Deviant Behaviors as Expressed by Married Adults in Ilorin Metropolis - Adegunju, Kabir Adewale (Mimbar Sekolah Dasar, 2020)
Deviant behavior is detrimental to adolescents, and parental monitoring is necessary to forestall this act. Consequently, this study investigated the influence of parental monitoring on adolescents' deviant behavior as expressed by married adults in the Ilorin metropolis. This study also investigated moderating variables, including gender, age, family type, and religion, on the respondents' view. It employed a descriptive survey method where 200 married adults were selected through simple random and purposive sampling techniques. The participants responded to a questionnaire titled 'Influence of Parental Monitoring on Deviant Behavior Questionnaire' (IPMDBQ).' The instrument's validity was conducted by a team of five experts from Nigeria, and the reliability yielded a correlation coefficient of 0.72. Besides, t-test and ANOVA statistical tools were employed to test the hypotheses at an alpha level of 0.05. The result revealed a positive influence of parental monitoring on adolescents' deviant behavior. It was found that there was no significant difference in the respondents' views based on gender, age, family type, and religion. Therefore, it is recommended that parents should monitor their wards appropriately to forestall deviant behavior among adolescents in Nigerian society.